Brand Image, Harga dan Ketepatan Waktu Pengiriman Terhadap Keputusan Pembelian - Muhammad Haikal Aliftian Nantigiri; Sri Handayani; Veronica Veronica (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
This study aims to determine the effect of brand image, price, and timeliness of delivery on purchasing decisions at J&T Express Bekasi branch in 2021. The research method used is quantitative methods and data collection methods using a survey method with a questionnaire. The sampling technique in this study used probability sampling with a simple random sampling approach, using 100 respondents. The test was carried out using the SPSS version 21 program.The result of this study indicates that brand image has a positive and significant influence on purchasing decisions where the results of the partial test show that Ho is rejected and Ha is accepted, meanwhile the price did not have a positive and significant effect on purchasing decisions whereas the results of the partial test show that Ho is accepted. and Ha is rejected, and timeliness of delivery has a positive and significant effect on purchasing decisions where the results of the partial test showed that Ho is rejected and Ha is accepted. As a simultaneous test results showed that brand image, price, and timeliness of delivery have a positive and significant influence on purchasing decisions where the results of the simultaneous test show that Ho is rejected and Ha is accepted. Suggestions given in this study include the company is expected to always improve the quality of service related to company employees in serving consumers and improve the quality of delivery of goods so that there are no delays